Gender Differences in Poverty in Colombia - Buitrago, Paola; Muller, Miriam; Olivieri, Sergio; Pico, Julieth (World Bank, Washington, DC, 2019)
This note presents the gender poverty profiles for Colombia using a lifecycle approach. In Colombia, as in the vast majority of countries around the world, girls and boys are consistently poorer than adults and seniors. Notwithstanding, the difference on poverty rates between women and men during their reproductive age in Colombia is around 6 p.p. while in the world is around 2 p.p. Another interesting finding is that the likelihood of being poor diminishes with formal education, for both women and men. Nevertheless, as the level of formal education increases, the share of women among the poor do so also. This note is organized as follows: section one presents the poverty rates for women and men, by education level, marital status, location, and employment type. Section two presents the results of the lifecycle approach. The authors present the gender poverty profile when variables as age, demographic, and economic composition are combined with gender, to define the profiles. And finally, section three presents some final remarks.